A Description Of Students E-Learning Satisfaction During Covid-19 Pandemic On University Muhammadiyah Gombong - Sulistiowati, Puput; Purwanti, Ery; Susilowati, Yuli (Prosiding University Research Colloquium, 2022)
Background: During the Pandemic Period, the policies of the Central Government and the Kebumen Regency Government make learning process on University Muhammadiyah Gombong have to be conducted online from home. The learning process can be accessed by Zoom, Google Meeting, Google Classroom, and Whatsapp Groups media. Students felt something problems during electronic learning where students were not understanding, especially clinical skills laboratory. This case makes the students unsatisfied. Purpose: To describe students’ satisfaction on e-learning process during COVID- 19 pandemic on University Muhammadiyah Gombong. Method: This research was a descriptive quantitative method. Research samples were of eighty-nine students of the bachelor and diploma nursing program of University Muhammadiyah Gombong. They were recruited by proportionate random sampling. Result: The most of respondents’ ages were twenty years old, thirty respondents (33.7%). Seventy-eight of respondents were female (87.6%), and twenty-six respondents were the first year. Conclusion: Fifty-four students were satisfied enough category (60.7%) against the e-learning process